Clinicopathology profile evaluated against several risk factors in breast cancer cases (Medical Journal of Indonesia, 1999)
Telah dilakukan penelitian dua ratus dua puluh enam kasus kanker payudara (KPD) yang berhubungan dengan aspek klinik dan patologi serta faktor risiko yang berhubungan dengan terjadinya keganasan payudara. Distribusi terbanyak pada umur antara 35-55 tahun dengan frekuensi tertinggi antara umur 40-50 tahun. Tidak didapatkan perbedaan lokasi tumor pada payudara kanan atau kiri serta distribusi pre-menopause maupun post-menopause. Delapan puluh satu koma enam persen KPD ditemukan pada stadium lanjut (stadium llf A: 17,7%, JJJB: 56,2% dan JV: 11,9%), sedangkan stadium !: 1,3% dan stadium fl: 11,9%. Tujuh puluh Lima dari 226 kasus dilakukan tindakan pembedahan: 60% mastektomi simpel, 26,7% mastektomi radikal dan 1,3%: breast concerving treatment (BCT). His topatologi dari jaringan payudara dari 214 kasus didapatkan karsinoma invasif yang terdiri dari: 90,4% karsinoma duktal invasif dan 9,6% tipe khusus. Dilakukan analisa dari beberapa faktor risiko seperti status kawin, umur pada saat kawin pertama, umur menarche, status menopause, laktasi, riwayat keluarga KPD, penggunaan kontrasepsi dan konsumsi tinggi lemak. Hasil dari metode kasus kontrol menunjukkan bahwa faktor-faktor status menopause, laktasi dan konsumsi tinggi lemak meningkatkan risiko terjadinya KPD, dengan risiko relatif masing-masing: 1,51, 1,83 dan 2,61. Abstract The second batch case-control study on breast cancer has been conducted as a joint study between Indonesian and Japan. Two hundred and twenty six ( 226) cases of breast cancer was collected to assess the risk factors and evaluated for their clinical presentation of the disease. The age distribution in some high risk areas showed at age 35 to 55 years, with a single peak between 40 to 50. There was no difference in number of cases in respect to tumor site and menopausal status. The majority of cases 81.6 % were in advanced stage ( l!JA: 17.7%, JflB: 56.2% and JV: 11.9%) while in contrast stage l and fl were very rare (1.3% and 11.9% respectively ). Only 75 cases were operable; simple mastectomy was the most frequent surgery carried out (60.0%), followed by modified radical mastectomy (26.7%), classical radical mastectomy (12%) and breast conserving treatment (1.3%). The specimens were reviewed using classification recommended by the Japanese Breast Cancer Society revealed invasive ductal carcinoma (90.4%) and the special type (9.6%) . Several risk factors were analyzed for their influence to the development of breast cancer; namely: marital status, age at first marriage, menarche, menopausal status, lactation, family history of breast cancer; use of contraceptive and fat consumption. Among the characteristics studied, the following factors significantly increased the risk of breast cancer: menopausal status (RR= 1.51; 95% Cl: 1.10-2.09), non-lactating children (RR=1.83; 95% Cl: 1.07-3. Jl ) and fat consumption (RR=2.61; 95% Cl: 1.86-3.68), while the use of contraceptive showed pro tective effect. The findings will be discussed in its benefit relative to both the improvement of the treatment modality and the cancer control prog ram. Keywords: Breast cancer, clinicopathological, case-control study, epidemiology